Impact of Clinical Pharmacist Diabetes Clinic on the Improvement of Health Outcomes in Type 2 Diabetes Subjects - AlSubaie, Nawal; Alsallal, Mohannad; AlTwaijri, Sulaiman; AlOtaibi, Ahmed; AlHarbi, Bandar; AlEissa, Mohammad; Alrashedi , Rana (Open Access Macedonian Journal of Medical Sciences, 2022)
AIM: This study aimed to evaluate the improvement of HbA1c, lipid profile, blood pressure readings, and weight in type 2 diabetes at the clinical pharmacist diabetes clinic (CPDC) in ambulatory care clinic. METHODS: A retrospective study was conducted at a CPDC; the clinical pharmacist role was to follow-up the referred uncontrolled type 2 diabetes patients and providing comprehensive management. RESULTS: A total of 419 patients were included the study. The mean ± standard error of the mean (SEM) age was 58.9 ± 0.59 years old. Sixty-two percent of the patients were female. At baseline, mean HbA1C ± SEM was 10.69% ± 0.06%, mean low-density lipoprotein (LDL) ± SEM was 2.66 ± 0.04 mmol/l. After 3 months of follow-up, HgbA1C had a statistically significant improvement by a reduction of 1.69% to be 9% ± 0.09% (95% confidence interval [CI] [1.50–1.87], p < 0.001). Moreover, mean HbA1C had a statistically significant improvement after 6 months of follow-up compared to baseline by 1.78% to be 8.9% ± 0.21% (95% CI [1.33–2.22], p < 0.001). LDL had a statistically significant improvement after 3 months by 0.24 mmol/l to be 2.42 ± 0.04 mmol/l (95% CI [0.15–0.35], p < 0.001) and after 6 months of follow-up by 0.28 mmol/l to be 2.38 ± 0.04 mmol/l (95% CI [0.20–0.36], p < 0.001). CONCLUSION: The results stated that the clinical pharmacist anticipated care is achievable and had significant effect in the reduction of HbA1C and LDL levels in patients with uncontrolled type 2 diabetes.